Marital attitude mahasiswa ditinjau dari kondisi pernikahan orang tua - Nisa Fitriani (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2023)
Abstract: In previous research, differences in marital attitudes have been examined among students with divorced and harmonious parents. However, unlike previous studies, this research seeks to test the differences in marital attitudes among students not only based on the marital status of their parents (divorced or intact) but also based on the quality of their parents' relationship (harmonious or conflicted). The chosen method of analysis is a comparison test. The sample for this study consists of IAIN Kediri students aged 18-23 years. Using quota sampling, a total of 123 students were obtained. From the total number of students, they were divided into three categories: students with divorced parents, students with intact parents but in conflicted relationships, and students with harmonious parents. The number of respondents in each category was 41 students. The measurement tool used was the General Attitudes Toward Marriage Scale (GATM). Data analysis in this study employed ANOVA. The test results indicated differences in marital attitudes among students with harmonious parents, intact but conflicted parents, and divorced parents. The implications of this study suggest that practitioners in related fields should develop appropriate premarital guidance programs for students to acquire information and cultivate more positive marital attitudesKeywords: marriage attitudes; parents' marital conditions; parents